2012
DOI: 10.1371/journal.pone.0038925
|View full text |Cite
|
Sign up to set email alerts
|

The Type III Secreted Protein BspR Regulates the Virulence Genes in Bordetella bronchiseptica

Abstract: Bordetella bronchiseptica is closely related with B. pertussis and B. parapertussis, the causative agents of whooping cough. These pathogenic species share a number of virulence genes, including the gene locus for the type III secretion system (T3SS) that delivers effector proteins. To identify unknown type III effectors in Bordetella, secreted proteins in the bacterial culture supernatants of wild-type B. bronchiseptica and an isogenic T3SS-deficient mutant were compared with iTRAQ-based, quantitative proteom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
62
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(68 citation statements)
references
References 45 publications
6
62
0
Order By: Relevance
“…In WT RB50, overexpression of btrA decreased expression of T3SS-associated genes but did not confer increased expression of toxin or adhesin loci, suggesting that BtrA levels in RB50 are sufficient for maximal expression under laboratory conditions. Together, these data confirm and extend previously published results (28) and show that BtrA differentially regulates three distinct modules of the BvgAS regulon: (i) Bvg + phase adhesin and toxin genes, which require BtrA for full level expression, (ii) Bvg + phase T3SS loci that require BtrS and are repressed by BtrA, and (iii) the Bvg phase flagellin locus, which is down-regulated by BtrA (Fig. 1G).…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…In WT RB50, overexpression of btrA decreased expression of T3SS-associated genes but did not confer increased expression of toxin or adhesin loci, suggesting that BtrA levels in RB50 are sufficient for maximal expression under laboratory conditions. Together, these data confirm and extend previously published results (28) and show that BtrA differentially regulates three distinct modules of the BvgAS regulon: (i) Bvg + phase adhesin and toxin genes, which require BtrA for full level expression, (ii) Bvg + phase T3SS loci that require BtrS and are repressed by BtrA, and (iii) the Bvg phase flagellin locus, which is down-regulated by BtrA (Fig. 1G).…”
Section: Resultssupporting
confidence: 91%
“…Recent studies implicate BtrA (also called BspR), which is encoded directly upstream of btrS, as an exported substrate of the Bsc T3SS, illustrated in Fig. 1B using B. bronchiseptica strain RB50 grown in vitro under conditions permissive for type III secretion (20,28). BtrA and Bsp22, a known T3SS substrate (26), are exported into supernatants in a manner dependent on the BscN ATPase.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Its product, BspR, is one of the T3SS secreted proteins that is translocated into host cell nuclei and is also a negative transcriptional regulator of T3SS genes in the bacterial cytosol (26). To assess the effect of BspR on the expression of the T3SS, the levels of BspR were analyzed by immunoblotting.…”
Section: Consumption Of Glutamate In the Mediummentioning
confidence: 99%
“…BteA, which triggers cytotoxicity in a wide variety of cultured cell lines , is translocated into the host cells via 48 aa residues at its N‐terminal. We reported in 2012 that BspR acts as a transcriptional regulator that positively and negatively regulates various virulence and non‐virulence genes . More recently, we observed that BspR is translocated into the nuclei of infected cells .…”
mentioning
confidence: 99%